2016
DOI: 10.1111/jog.13253
|View full text |Cite
|
Sign up to set email alerts
|

Combined spinal‐epidural anesthesia with hypobaric ropivacaine in sitting position significantly increases the incidence of hypotension in parturients undergoing cesarean section

Abstract: As compared to the lateral positions, CSEA with hypobaric ropivacaine in the sitting position is more likely to cause hypotension and excessively high block level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
2
7
1
Order By: Relevance
“…Our finding is very close to the results of Chantal T. Crochetière et al who found a hypotension rate of 13.6% [32] . However, our result is different from some findings in previous studies [33] that found 72%,36%,40% with sitting, right lateral, and left lateral patients' position, respectively. Using the same LA and hypotension criteria, but in sitting position during epidural puncture, E. Bjornestad et al [29] found a hypotension incidence of 75%, and 50% with 2-chroroprocaine in epidural-use.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding is very close to the results of Chantal T. Crochetière et al who found a hypotension rate of 13.6% [32] . However, our result is different from some findings in previous studies [33] that found 72%,36%,40% with sitting, right lateral, and left lateral patients' position, respectively. Using the same LA and hypotension criteria, but in sitting position during epidural puncture, E. Bjornestad et al [29] found a hypotension incidence of 75%, and 50% with 2-chroroprocaine in epidural-use.…”
Section: Discussioncontrasting
confidence: 99%
“…Lateral position results in little vagal reflex and thus decreased hypotension rate. This view is supported by Fuyi Shen et al and Obasuyi and co-authors [30,33] who claimed a little hypotension rate with lateral position in ropivacaine combined epidural-spinal and bupivacaine spinal anesthesia for CS. With the same hypotension criteria like in our study, a SA study [28] resulted in more than 71% of hypotension incidence.…”
Section: Discussionmentioning
confidence: 76%
“…The incidence of spinal anesthesia-induced hypotension observed in this study was 21.88%. This result is consistent with previous studies that controlled sensory block level and ascension rate while administering isobaric ropivacaine in the rightlateral position (13,14).…”
Section: Discussionsupporting
confidence: 93%
“…The slow ascension rate of the sensory block level results in a low incidence of hypotension; this is because of the fact that a slower-onset sympathetic block allows more time for physiological compensation. Furthermore, body position, and the density of anesthetics delivered locally, are considered to represent important factors that are related to spinal anesthesia-induced hypotension (14). In this study, pregnant women received spinal-epidural anesthesia whilst lying in the right-lateral position.…”
Section: Discussionmentioning
confidence: 99%
“…Ngan reported a higher ED 95 of intrathecal ropivacaine than our results, even without phenylephrine infusion. [13] As we have known, the required dose of spinal anesthetic for cesarean section is influenced by several factors such as the maternal position during performing anesthesia, [14,15] speed of injection of intrathecal solution, [16] gravity of intrathecal solution, [17] race of parturients, [14] co-administration of intrathecal opioids [18] and so on. Between our present study and Ngan et al [13] study, there were several differences in maternal position during performing spinal anesthesia (lateral vs sitting), race, intrathecal opioids (without vs with fentanyl) existed.…”
Section: Discussionmentioning
confidence: 99%